Experimental research on the evolutionary characteristics of acoustic signals for concrete cracking under uniaxial compression. (30th March 2022) - Zhao, Guofu; Luo, Danni; Su, Guoshao; Chen, Bingrui; Huang, Jinghua
Highlights: Exploring the features of the AE, MS, and sound released during concrete cracking. Proposing a method to determine the initial stress of activeness of acoustic signals. Obtaining the damage evolutionary equations based on acoustic signals. Abstract: In this study, the evolutionary characteristics of the acoustic emission (AE), microseismic (MS), and sound signals released during concrete fracture in terms of their amplitude, b value, activity level, and frequency spectrum were investigated. The results indicated that the b values are all characterised by a continuous decline immediately before concrete failure, accompanied by the appearance of low-frequency signals with high amplitudes. The occurrence of these two phenomena can be used as precursor information for the subsequent concrete failure. Nevertheless, there are significant differences among the three signal types. Frequency ranges of these acoustic signals and hierarchical characteristics of the concrete fracturing result in different signal activeness, which can be evidenced by the following order of the initial stress of activeness: sound (85% σpeak ), MS (70% σpeak ), and AE (57% σpeak ). Diversities in signal acquisitions modes lead to differences near the failure stage. A quiescent period of AE, characterized by only a few signals with low frequency and high amplitude, was observed immediately before concrete failure, whereas MS and sound were distributed in various frequency bands without quiescent periods. These differences indicated that the three types of signals have different sensitivities and applicability. A reliable concrete fracturing analysis and prediction can be achieved by the integrated usage of the three types of acoustic techniques.